Writing scientific research articles : strategy and steps - Cargill, Margaret; O'Connor, Patrick , 1967- (Wiley-Blackwell, 2013)
This text guides authors in how to write, as well as what to write, to improve their chances of having their articles accepted for publication in international, peer reviewed journals